TV on your mobile: the next big thing? designing content for cell TV / Baharuddin Hj. Aziz - Aziz, Baharuddin (Centre for Media and Information Warfare Studies, 2009)
Recent developments in telemedia delivery systems, especially in terms of speed and capacity, have spawned newer avenues through which mass-mediated messages and creative content can be disseminated to consumers. Cell TV -- television on your cell phone – is currently drawing a significant amount of attention and discussion. It is being touted as “the next big thing in the next decade”. Will it be successful? Or will it be just another business hype enabling telcos (or whoever) to raise cash with venture capitalists only to see their oft-celebrated technology and attendant services never really getting off the ground and, concomitantly, getting themselves into the red?